Peran Komunikasi Media Sosial Dalam Meningkatkan Kesehatan Mental - Efendi, Erwan; Salam, Muhammad Abrar Haq; Daffa, Muhammad; Sanjaya, Shendy; Azmi, Rifka Nur (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2023)
Mental health is a person's state of life, namely a state of self-evaluation of one's feelings, including aspects such as self-esteem, physical strength, self-control ability, etc. Mental health is a person's ability to deal with stress or depression. On this occasion, according to mental health, it is an optimal combination or harmony between various mental activities and the ability to deal with simple mental problems that a person faces, as well as the ability to feel feelings of happiness and good strength. But many people are now unable to maintain mental health due to increasing depression. The researcher's research method uses a qualitative approach. This qualitative approach was taken to obtain more accurate and meaningful data. Research using a qualitative approach method used by researchers is library research, namely a series of activities relating to library data collection methods starting from books, scientific works, and national journals. The conclusion from this research is that social media is very important in the spread of mental health. It can be seen from the data above that almost all people in the modern era now use social media, from children and teenagers to the elderly. Various social media content that talks about mental health can get a lot of followers and can help them recover from the depression they are experiencing.